Childhood IgA Vasculitis (Henoch Schonlein Purpura)—Advances and Knowledge Gaps - Oni, Louise; Sampath, Sunil (Frontiers in Pediatrics, 2019)
Immunoglobulin A vasculitis (IgAV; formerly Henoch Schonlein Purpura) is the most common form of childhood vasculitis. It can occur in any age and peaks around 4-6 years old. It demonstrates seasonal variation implicating a role for environmental triggers and geographical variation. The diagnosis is made clinically and 95% of patients will present with a rash, together with any from a triad of other systems – gastrointestinal, musculoskeletal and renal. Most cases of IgAV in children have an excellent outcome. Treatment may be required during the acute phase for gastrointestinal involvement and renal involvement, termed IgAV nephritis (previously HSP nephritis), is the most serious long-term manifestation accounting for approximately 1-2% of all childhood end stage kidney disease. It therefore requires a period of renal monitoring conducted for 6-12 months. Patients presenting with nephrotic and/or nephritic syndrome or whom develop significant persistent proteinuria should undergo a renal biopsy to evaluate the extent of renal inflammation and there are now international consensus guidelines that outline the indications for when to do this. At present there is no evidence to support the use of medications at the outset in all patients to prevent subsequent renal inflammation. Consensus management guidelines suggest using oral corticosteroids for milder disease, oral or intravenous corticosteroids plus azathioprine or mycophenolate moefetil or intravenous cyclophosphamide for moderate disease and intravenous corticosteroids with cyclophosphamide for severe disease. Angiotensin system inhibitors act as adjunctive treatment for persisting proteinuria and frequently relapsing disease may necessitate the use of immunosuppressant agents. Renal outcomes in this disease have remained static over time and progress may be hindered due to many reasons, including the lack of reliable disease biomarkers and an absence of core outcome measures allowing for accurate comparison between studies. This review article summarises the current evidence supporting the management of this condition highlighting recent findings and areas of unmet need. In order to improve the long term outcomes in this condition international research collaboration is urgently required.